2018
DOI: 10.1002/jcp.27278
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative potential of antidiabetic agents: A possible protective mechanism against vascular complications in diabetic patients

Abstract: Many vascular complications are related to exposure of tissues to elevated levels of glucose, a condition that promotes oxidative stress. The primary goal of antidiabetic medication is for normalization of blood glucose. However, antidiabetic medications may have antioxidant effects that go beyond their hypoglycemic influences. Therefore, antidiabetic drugs may be doubly beneficial in preventing diabetic complications. Vascular dysfunction due to uncontrolled diabetes is a serious complication of the disease a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 130 publications
(205 reference statements)
0
52
0
5
Order By: Relevance
“…Increased presence of inflammation, as evidenced either by its cellular make-up or by its molecular repertoire, has been described in many tissues of diabetic humans or animals. [15][16][17][18][19][20] Furthermore, many diabetic complications have been associated with several specific inflammatory cytokines. 32,33 Up to this study, local diabetes-induced inflammation was identified in the membranes only by the presence of mononuclear inflammatory cells and indirectly by the anti-degradative effect of impregnation in TC and HA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased presence of inflammation, as evidenced either by its cellular make-up or by its molecular repertoire, has been described in many tissues of diabetic humans or animals. [15][16][17][18][19][20] Furthermore, many diabetic complications have been associated with several specific inflammatory cytokines. 32,33 Up to this study, local diabetes-induced inflammation was identified in the membranes only by the presence of mononuclear inflammatory cells and indirectly by the anti-degradative effect of impregnation in TC and HA.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Common to most diabetic complications is a dysregulated inflammatory process, which manifests itself in excessive production of pro-inflammatory cytokines such as TNF , IL-1 , and IL-6, together with increased numbers of immune cells, such as neutrophils and macrophages. [12][13][14] Increased presence of inflammation, as evidenced either by its cellular or molecular repertoire, has been described in many body tissues, including skin, 15 gingiva and periodontal tissues, 16,17 retinae, 18 blood vessels, 19 and bones 20 of diabetic humans or animals. As expected from an exaggerated, dysregulated inflammatory state, many of the diabetic complications are associated with increased expression and production of collagenolytic enzymes, including matrix metalloproteinases (MMPs) 21 and cathepsins.…”
mentioning
confidence: 99%
“…Oxidative stress develops when the rate of free radical generation exceeds the antioxidant defense systems resulting in the toxic effects of free radicals [9,10]. Free radical species are important physiological components in biological homeostasis [11,12], but when their production increases excessively and greater than the body's antioxidant capacity, then oxidative stress results [12]. Oxidative stress is a major upstream event for diabetes complications as well as insulin resistance development [12][13][14], inducing pathophysiologic molecular mechanisms and initiating a cascade of deleterious pathways leading to insulin resistance and DM [8,15].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes and its associated complications have a substantial economic burden on health systems in most countries [5,6]. Many pharmacological agents have been developed to improve hyperglycemia and prevent complications associated with diabetes [7]. Imeglimin is a novel and promising antihyperglycemic agent but has not been approved yet for managing patients with diabetes [8,9].…”
Section: Introductionmentioning
confidence: 99%